Application of the Picture and Picture Type of Cooperative Learning Model in Improving Student Learning Creativity - Siregar, Nurliani; Siregar, Hisar; Hutahaean, Hasahatan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
This study aims to see to what extent the application of the Picture and Picture cooperative learning model increasing students creativity at SMP Negeri 8 Pematang Siantar. The number of sempel as many as 40 people. This study used an experimental method, the data analysis technique used parametric statistics, namely the normality test used the chi square test, the homogeneity test used the F-test and the hypothesis test used the t-test. To find out to what extent the application of the Picture and Picture Cooperatif Learning Model in PAK Learning in Improving Student Creativity in Learning, the data analysis shows that the learning outcomes data are normally distributed and also homogeneous. Student creativity in the experimental class was higher than the control class, namely 142>125.8. The difference in student creativity between the experimental class and the control class is also significant because the results of the difference test (t test) obtained tcount greater than t table with a significant level of 5%, namely 2.779> 2.026. It can be conclude that the application of the Picture and Picture type of cooperative learning model has a significant effect on increasing the learning creativity of grade VII student at SMP Negeri 8 Pematang Siantar